2014
DOI: 10.1016/j.healthplace.2013.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of a community hospital closure on older adults: A focus group study

Abstract: The closing of hospitals has exacerbated challenges for older adults in accessing healthcare, especially those living in economically underserved settings. Through focus groups and a community-engaged approach, our study examined and documented the emergent health needs of older adults following the closing of a local hospital in an economically disadvantaged community. Focus groups were reconvened to assess progress and health needs over time. Analyses of the focus groups (n=37, mean age 77, 84% female) illus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…21,22 For example, qualitative studies have demonstrated that hospital closure may be associated with feelings of abandonment and social isolation, increased transportation challenges, and concern and uncertainty about how to access health services among adults in a community with a closure. [23][24][25] Our findings are consistent with prior work identifying predictors of hospital closure [11][12][13][14] and emergency department closure. 26 However, these studies did not examine the impact of closure on patient outcomes.…”
Section: Discussionsupporting
confidence: 88%
“…21,22 For example, qualitative studies have demonstrated that hospital closure may be associated with feelings of abandonment and social isolation, increased transportation challenges, and concern and uncertainty about how to access health services among adults in a community with a closure. [23][24][25] Our findings are consistent with prior work identifying predictors of hospital closure [11][12][13][14] and emergency department closure. 26 However, these studies did not examine the impact of closure on patient outcomes.…”
Section: Discussionsupporting
confidence: 88%
“…Rural hospitals can leverage their strong relationships with local communities and patients; they have also a significant positive influence on health of the population. When a hospital is closed, patients are forced to seek a new provider, which sometimes means a break in therapy [33]. A remote location also generates costs of transport, if it is available at all.…”
Section: Rural Hospitals As Part Of a Sustainable Health Systemmentioning
confidence: 99%
“…Future hospitals may overcome complacency and implement good Medicare billing practices to ensure reimbursement of legitimate claims by aligning with the top approaches identified within the scope of this study. Hospitals who have successfully implemented strategies to ensure they collect reimbursement for legitimate Medicare claims can increase growth in revenue, improve patient health outcomes, support job growth and reduce unemployment, ensuring they remain operational and convenient to members of the community (Armit & Oldham, 2015;Countouris et al, 2014).…”
Section: Importance Of the Problemmentioning
confidence: 99%
“…The maximization of reimbursement will ensure that community hospitals remain operational and continue to offer services to patients. Providing safe and convenient health care is an essential element for community hospitals (Countouris, Gilmore, & Yonas, 2014). This paper contains the exploration of strategies hospitals can implement to ensure the billing manager, along with other hospital staff, can make sure convenient hospitals stay open by applying best practices to address the risk brought on by changing regulations.…”
Section: Introduce the Problemmentioning
confidence: 99%